A Survey on the Role of the Irony-Based Technique in Beraat Etehlal in the Book" Nafsat-al-Madsur" - Hosein Hasanpour Alashti; Mostafa Mirdar Rezaei; Rahil Mohammadi deh abasani (مطالعات زبانی و بلاغی)
The modification in language by the artist, creates an image; this transformation is shaped by the use of elements that are in the context of existing language and its inherent capabilities. With the discovery and utilization of these tools, artificer modifies the natural norms of the language and, through this manipulation, creates the image of creation. From this perspective, the book "Nafsat-al-Madsur" is full of fascinating imagery; On the other hand, how to start a speech and editing it in order to effect on the reader, has an important and determinative role, and the author can write the appropriate beginning, while also being able to duplicate the influence of his book. He also puts the reader in the background of the work and its concept. One of the finest and most influential techniques in this regard is the use of the primitive craft of the “opening the future”. In the book titled " Nafsat-al-Madsur", the author uses this technique twice: first, on the first page of the book, that contains  "three-pages" full text, two words "sword" and " The pen " is seen at the center of the author's imagery; the second “opening the future”  is seen almost in the middle of the book, in which author's illustrations are sequentially followed by various phenomena (like the Sky, the earth, aurora, morning, mountain and sea). One of the many types of imaging tools that Nasawi uses at the beginning of his speech to apply his image to transform his mental imagery into an image. This survey attempts to define, in addition to defining syntactic manifestations, two types of it, namely, the "amphibology metaphor irony” and "irony metaphor", which in the creation of images have an important role.